2019
DOI: 10.1177/0003702819860121
|View full text |Cite
|
Sign up to set email alerts
|

Improved Vancouver Raman Algorithm Based on Empirical Mode Decomposition for Denoising Biological Samples

Abstract: A novel method based on the Vancouver Raman algorithm (VRA) and empirical mode decomposition (EMD) for denoising Raman spectra of biological samples is presented. The VRA is one of the most used methods for denoising Raman spectroscopy and is composed of two main steps: signal filtering and polynomial fitting. However, the signal filtering step consists in a simple mean filter that could eliminate spectrum peaks with small intensities or merge relatively close spectrum peaks into one single peak. Thus, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The modified Vancouver Raman algorithm (mVRA) is a novel method to remove fluorescence in biological Raman spectra, proposed by Le on-Bejarano et al [20] The mVRA showed good results with respect to other methods with improvements such as the automatization of baseline correction using Empirical Mode Decomposition, and the denoising of Raman spectra by a nonlinear filter based on Empirical Mode Decomposition; thus, the method does not require adjustment of parameters to correct the baseline preserving the inherent variability on the signal. The results of mVRA suggest that the technique is a good alternative for processing complex Raman spectra, especially for biological samples.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…The modified Vancouver Raman algorithm (mVRA) is a novel method to remove fluorescence in biological Raman spectra, proposed by Le on-Bejarano et al [20] The mVRA showed good results with respect to other methods with improvements such as the automatization of baseline correction using Empirical Mode Decomposition, and the denoising of Raman spectra by a nonlinear filter based on Empirical Mode Decomposition; thus, the method does not require adjustment of parameters to correct the baseline preserving the inherent variability on the signal. The results of mVRA suggest that the technique is a good alternative for processing complex Raman spectra, especially for biological samples.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…The most commonly used method in biomedical skin tissue measurements is the Vancouver Raman Algorithm, which combines peak removal The spectra obtained with excitation at 532 nm contained a broad, exponentially decreasing fluorescence curve with prominent Raman peaks, so the most important step in Raman signal processing is the removal of the fluorescence background that is superimposed on the Raman signal. The most commonly used method in biomedical skin tissue measurements is the Vancouver Raman Algorithm, which combines peak removal with a modified polynomial fitting [28][29][30][31][32]. An example of the fluorescence background calculated by the Vancouver Raman Algorithm and the final Raman spectra smoothed by the Savitzky-Golay method are shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The measuring of Raman/PL spectra at 1064 nm has been widely used for the investigation of various human tissues, including tumors, without destruction (thermal damage, photo damage) [12,30,[32][33][34][35][36], because this wavelength is non-destructive and non-mutagenic. The Raman/PL spectra of normal skin, BCC and SCC were registered at 1064 nm laser excitation in the 900-3100 cm -1 range.…”
Section: Raman/pl Spectra At 1064 Nm Laser Photoexcitationmentioning
confidence: 99%
“…Boxcar averaging (BA) was used for high-frequency modulation of Raman noise [13]. Vancouver Raman algorithm (VRA), which is simple and effective, is a technique used to reduce fluorescence noise [14]. Three parameters of the boxcar averaging technique consisting of boxcar width order, integration time, and scan average, were used to find the optimum condition that provided good signals.…”
Section: Introductionmentioning
confidence: 99%